DMS Implications for Universities - Bresfelean, Vasile Paul; Mocean, Loredana; Urean, Claudia Andreea (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Organizations have long been struggling with the large amount of paper documents to be effectively administered, stored and organized so as to allow their easy and fast retrieval. Furthermore, energy and paper costs, security, destruction or loss and the volume of space occupied by numerous documents, folders and cabinets are also challenging problems. Digitization of paper documents and Document Management Systems (DMS) emerged as a solution to these issues with numerous advantages (eco-friendly, decreased operational costs, increased productivity, better and fast service etc.) leading to more efficient organization processes. Cloud storage and applications are an up-to-date approach with lower costs for higher education institutions, which aspire to enhance their documents and records management from creation throughout their whole lifecycle (store, capture, distribute, retrieve). While knowledge management (KM) has a demanding mission in higher education institutions, ontologies are another novel ground for document management applications in education. This paper is an extended version of our latest research study [4] and aims to extend our university’s existing applications to a multifaceted Document Management System-as-a-Service (DMSaaS) with many benefits for the institution, where records and documents are to be managed based on novel technologies. DMSaaS can address the issues related to cost, environment, space, security, operability better than a classic DMS.